Equality, equity, or inequality duplication? How preschoolers distribute necessary and luxury resources between rich and poor others. Issue 1 (18th July 2019) - Essler, Samuel; Lepach, Anja C.; Petermann, Franz; Paulus, Markus
Abstract: The present study investigated preschoolers' multiple sociomoral considerations (equality, equity, and perpetuating inequality) in a third‐party context of social inequality. Using a resource allocation task involving one wealthy and one poor character, we examined how 3–5‐year‐old children ( N = 100) allocated either necessary (must‐have) or luxury (nice‐to‐have) resources. In addition, preschoolers' emotions, reasoning, and judgments were assessed. Results indicated that preschoolers distributing more resources to wealthy than poor others displayed a decision‐making pattern distinct from preschoolers allocating equally or equitably and largely matched the numeric proportions of the inequality in their allocations. In addition, preschoolers were sensitive to the differential implications of necessary and luxury resources, thereby considering others' needs in their moral decisions. Emotions were related to reasoning, but did not mediate the relationship between judgment and behavior. These findings demonstrate novel aspects of preschoolers' multifaceted moral considerations in the context of resource inequality.